Tensile resistance of bolted angle connections in the beam-column joint against progressive collapse. (1st June 2021) - Zhang, Ying; Wang, Jingxuan; Gao, Shan; Wang, Sheliang; Fu, Feng
Highlights: 20 specimens were tested with the observation of five kinds of failure modes. Angle thickness, horizontal and vertical bolt pitch affected the failure mode of the connection. Significant plastic deformation appeared in both the horizontal and vertical legs. The prediction formulas for the performance of the connection are proposed. A mechanical model of bolted angle connection is established and verified. Abstract: In this paper, an experimental study was carried out on the bolted angle connection under uniaxial tension. The design parameters of the tested connections include angle thickness, bolt hole distribution, bolt diameter and bolt preload. In total 20 specimens were tested with five different kinds of failure modes observed. The experimental results showed that angle thickness, horizontal bolt pitch and vertical bolt pitch all affect the failure modes of the connections and are positively correlated with their ultimate bearing capacity. Significant plastic deformation appeared in both the horizontal and vertical legs of the angle. Based on the experimental results and the corresponding theoretical analysis, a mechanical model of bolted angle connection is proposed to predict its initial stiffness, ultimate bearing capacity and ultimate deformation and verified against the tested results and other mechanical models, in terms of uniaxial tensile load-displacement curves. The proposed model fits with the tested results better than other models.